Identifikasi Kondisi Drainase Berbasis WebGIS di Jalan Pangeran Antasari Kota Samarinda - Fernando Dwio Junianto; Shabri Indra Suryalfihra; Feri Fadlin; A. Arifin Itsnani SM (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to identify the condition of drainage channels located along Jalan Pangeran Antasari in Samarinda City and to present the data interactively through a WebGIS platform. Drainage issues in this area often cause waterlogging and flooding during heavy rainfall. Therefore, accurate and accessible mapping of drainage conditions is crucial. The research method involved physical measurements of drainage dimensions, such as top width, bottom width, channel height, and concrete width. The collected data were processed using ArcGIS Pro software by digitizing the drainage paths in the form of polylines, which were then published through ArcGIS Online in a dashboard format. Field documentation was also supported by geo-tagged photos that were converted into coordinate points on the map. The findings of the study revealed that several drainage segments have inadequate dimensions to accommodate stormwater during heavy rain, indicating the need for improvement or normalization. The developed WebGIS successfully presents spatial and descriptive information about the drainage conditions in an interactive format, making it a valuable reference for technical evaluation and drainage management planning in the area